Farmers (Empowerment and Protection ) Agreement on Price Assurance and Farm Service Act, 2020 - Universal (Gurgaon, LexisNexis, 2023)
Farmers (Empowerment and Protection ) Agreement on Price Assurance and Farm Service Act, 2020.
Keywords: Bare Act